PERLINDUNGAN HUKUM NOTARIS PENERIMA PROTOKOL ATAS AKTA PEMBERI PROTOKOL YANG DIBUAT OLEH DAN ATAU DIHADAPAN NOTARIS PENGGANTI - Erni Rosta Saragih; Dhody AR Widjajaatmadja; Erny Kencanawati (Bajang Institute, 2025)
Abstract : A retired Notary will basically submit the protocol of the Notarial deed that has been made during his/her term of office as a Notary to another Notary. However, the provisions of the Notary Law and other legal provisions do not regulate for the Notary Receiving the Protocol for the Protocol Provider's deed made by and/or before the Substitute Notary. The problem in this study is related to the responsibility of the Notary Receiving the Protocol for the provider's deed made by and/or before substitute Notary and the protection of the Notary Receiving the Protocol deed made by and/or before the substitute Notary. The research method used in this legal research is normative juridical legal research. The research approaches used in this legal research include statutory, conceptual, analytical, and historical approach. legal material analysis techniques used include analogical construction, grammatical interpretation, and systematic interpretation to analyze the problem based on the existing of the legal material for this legal studies. The results of this study indicate that a Notary has no responsibility for the deed made by a substitute Notary. Regarding the case of an error made by a substitute notary in making a deed that causes losses and the government or state or commits a disciplinary violation of the prohibitions or obligations as a notary, sanctions will be imposed according to applicable laws. Legal protection for Notaries receiving protocols for authentic deeds made by and/or before a substitute Notary is through the existence of a Notary Honorary Council. With the existence of a Notary Honorary Council in the event of any form of summons, examination and detention, it is carried out after obtaining permission from the Notary Honorary Council that has examined it first, so that in the end it will create legal certainty for the community with the trust that underlies authority.